Calibration of ALMA as a Phased Array. ALMA Observations During the 2017 VLBI Campaign. (28th May 2019) - Goddi, C.; Martí-Vidal, I.; Messias, H.; Crew, G. B.; Herrero-Illana, R.; Impellizzeri, V.; Rottmann, H.; Wagner, J.; Fomalont, E.; Matthews, L. D.; Petry, D.; Phillips, N.; et al.
Abstract: We present a detailed description of the special procedures for calibration and quality assurance of Atacama Large Millimeter/submillimeter Array (ALMA) observations in Very Long Baseline Interferometry (VLBI) mode. These procedures are required to turn the phased ALMA array into a fully calibrated VLBI station. As an illustration of these methodologies, we present full-polarization observations carried out with ALMA as a phased array at 3 mm (Band 3) and 1.3 mm (Band 6) as part of Cycle-4. These are the first VLBI science observations conducted with ALMA and were obtained during a 2017 VLBI campaign in concert with other telescopes worldwide as part of the Global mm-VLBI Array (GMVA, April 1–3) and the Event Horizon Telescope (EHT, April 5–11) in ALMA Bands 3 and 6, respectively.